Comparison of optimized operation of energy community's flexibility considering different regulations and trading structures - Khajeh, Hosna; Firoozi, Hooman; Laaksonen, Hannu; Shafie-khah, Miadreza (IET, 2021)
This paper provides a comparison of an energy community energy trading under different regulations and trading structures. In this regard, it considers three cases. In the first case, the community is imposed a fixed price for consuming energy and the community manager aims to maximize the comfort level of its members. In the second case, the community pays for its consumption according to the market prices. The goal of the community manager is to minimize the total costs of the whole community. Finally, regarding the third case, the community trades power based on the negotiated prices with the same goal as the second case. The proposed models are implemented on a hypothetical community with 20 households as a member and the flexibilities of community's flexible energy resources are calculated for each case.
Keywords: Energy community; flexibility; optimal operation; pricing regulation; fi=Sähkötekniikka|en=Electrical Engineering|